Phytochemical Constituents of the Stems of Styrax benzoides Craib and Their Chemosystematic Significance - Puttinan Meepowpan (Science Faculty of Chiang Mai University, 2019)
The first chemical investigation in the dichloromethane extract from Styrax benzoides stems has been reported. On the basis of chromatography, five compounds including erythrodiol-3-acetate (1), stigmasterol (2), (24R)-24-ethylcholesta-4,22-dien-3-one (3), 5-(3¢¢-hydroxy propyl)-7-methoxy-2-(3¢,4¢-methylenedioxyphenyl)benzofuran (4) and 5-(3¢¢-hydroxy propyl)-7-methoxy-2-(3¢,4¢-dimethoxyphenyl)benzofuran (5) were successfully isolated. The chemical structures of all refined compounds were elucidated by a combination of several spectroscopic results accompanied by comparison with the literature data. All five compounds were isolated for the first time in the species S. benzoides. The preliminary chemosystematic analysis suggests the close taxonomic relationship between S. benzoides and other species in the same genus such as S. camporum, S. officinalis, and S. ferrugineus. Benzofurans 4 and 5 may serve as significant chemotaxonomic markers of the genus Styrax.